Friends with benefits: The positive consequences of pet-friendly practices for workers’ well-being - Junça Silva, A. (2022)
Although there is evidence that pets may help individuals who are facing significant daily stressors, little is known about the benefits of pet-friendly practices for their owners’ well-being. Based on the social exchange theory and on the Rusbult investment model, we argue that organizational pet-friendly practices will be viewed as a source of support from an organization that increases workers’ organizational identification, which in turn will lead to higher levels of psychological well-being and life satisfaction. For this study, 208 working adults answered an online questionnaire. Results from the study showed that the more pet-friendly practices the higher the workers’ organizational identification, which led to higher indices of psychological well-being and life satisfaction. This study contributes to a better understanding of the human–animal interaction and how pets can function as a resource for individuals’ well-being at work.